On the transformation of a former worker’s colony Symbolic and social boundaries in the making - Fehér, Katalin (Socio.hu Társadalomtudományi Szemle, 2016)
The study analyses a segregated neighbourhood’s microcommunity embedded in a former industrial middle–sized town. Symbolic boundaries are constructed to differentiate people, spaces and social practices and to create categories and classifications for them, while social boundaries are the objectified and realized differentiations. Studying symbolic and social boundaries made by the residents of a former workers’ colony allows us to describe the dynamically changing relations within a socially and ethnically mixed poor neighbourhood, paying attention to those conditional factors of local structural, political and cultural context that determine the uniqueness of this location. Established and outsider groups are maintaining symbolic boundaries rooted in social boundaries, while ethnic boundaries are symbolically drawn between Roma and non–Roma residents of the colony. Key words: symbolic boundaries, social boundaries, exclusion, Roma settlement, poor neighbourhood